Examination of the complexation ability of different calixarene derivatives towards [223Ra]RaCl2 in a hospital radiopharmaceutical laboratory - Freesmeyer, Martin; Weigand, Wolfgang; Weisheit, Thomas (Nuklearmedizin - NuclearMedicine, 2018)
Aim: In this contribution we investigated the potential transfer of an established method for the synthesis of 223Ra-labelled calixarene complexes to a hospital radiopharmaceutical environment. For this purpose, commercially available [223Ra]RaCl2 solution in pharmaceutical grade (Xofigo®) was reacted with three calixarene derivatives. Methods: A wellestablished two-phase extraction method using a two-phase solvent system was performed for complexation of the radium ions with calixarenes under slightly basic conditions. Moreover, the complexation reaction was conducted in homogenous medium (water / THF) as well as under elevated temperature. Results: The investigated reaction conditions did not allow the isolation of the desired products. Analytical evidence for the presence of radium-calixarene species by means of activity measurement, TLC as well as HPLC could not been proven unambiguously. Conclusion: We address the non-conversion of the educts to the large excess of sodium ions in the used Xofigo® solution, what may explain the hampered reaction for all conducted experiments. Finally the transfer of the published complexation concept into a radiopharmaceutical routine environment was not successful.Ziel: Ziel der vorliegenden Arbeit ist es, eine bekannte Methode zur Synthese von 223Ramarkierten Calixaren-Komplexen zunächst auf ihre Reproduzierbarkeit zu prüfen und gegebenenfalls für die Anwendung in einem radiopharmazeutischen Arbeitsbereich einer Klinik zu adaptieren. Als Ausgangsnuklid wurde kommerziell verfügbares [223Ra]RaCl2 in pharmazeutischer Qualität (Xofigo®) eingesetzt. Dieses wurde mit verschiedenen Calixarenderivaten umgesetzt. Methoden: Die Komplexierungsreaktion wurde sowohl mittels einer in der Literatur beschriebenen Zwei-Phasen-Extraktion als auch in einem homogenen Lösungsmittelgemisch (THF/Wasser) bei schwach basischen Bedingungen durchgeführt. Weiterhin wurde die Reaktionstemperatur variiert. Resultate: Bei keiner der durchgeführten Umsetzungen konnte die Bildung des postulierten Produkts durch spezifische Analysenmethoden wie Aktivitätsmessung, Radio-Dünnschichtchromatographie-Scans sowie Hochleistungsflüssigkeitschromatographie (HPLC) nachgewiesen werden. Schlussfolgerungen: Das Ausbleiben der Komplexierung ist wahrscheinlich auf den extrem hohen Überschuss an Natriumionen in der verwendeten Xofigo®-Lösung zurückzuführen. Die Anwendung der publizierten Komplexierungsmethode in einem radiopharmazeutischen Kliniklabor ist nicht möglich.
Keywords: Radium dichloride; Calixarene